Outcome of Different Treatment Modalities in Non-caseating Granulomatous Mastitis: A Narrative Review - Nasrin, Shamima; Alam Ovi, Mir Rasekh; Arif, Abdus Salam; Hasan, Md Jahid (Anwer Khan Modern Medical College Journal, 2021)
Granulomatous mastitis (GM) is a benign inflammatory condition of breast disease that affects women of childbearing age with a history of breastfeeding. The rarity and complex pathophysiology make the diagnosis and management quite dilemmatic for clinicians. This review explored the available treatment options for the disease condition in light of the recent literature. Surgery alone, intervention with or without steroids, antibiotic therapy, abscess drainage, methotrexate therapy, and antibiotics are widely used in different settings. However, surgery (with or without steroids) showed a higher recovery rate along with a lower recurrence rate. Steroid therapy is promising, but its use is limited due to the higher number of recurrences. In addition, the use of methotrexate showed an increased remission rate, but the toxicity profile was still high. However, treatment outcome mostly depends on the severity of the disease and individual physical status, and therefore, a comprehensive evaluation of the patients is crucial. This review recommended the formulation of a standard guideline for uniform management of granulomatous mastitis conditions in our country. AKMMC J 2022; 13(1) : 47-51